Application of Complex Additive from Peat Wastes and Sediments of Chemical Water Treatment of Thermal Power Plant in Production of Ceramic Bricks - Aliaksandr Hrachanikau; Andrei Kauchur; Pavel Manak; Ivan Tsimanov (Vestnik of Vitebsk State Technological University, 2023)
The purpose of the work was to assess the effectiveness of using a composite additive based on the sediments of chemical water treatment of thermal power plants and coal-containing components (peat) in the manufacture of ceramic bricks. The feasibility of using peat-containing components in combination with non-calcined sediments of chemical water preparation of thermal power plants as an additive to the ceramic mass in the production of various products is considered. Solution of technical problem is presented by additionally introducing peat with fraction of 0.5–5 mm in amount of 2–3.5 wt% and non-calcined sediments of chemical water preparation of heat and power plants in amount of up to 10 wt% into standard ceramic mass for production of building bricks. At Obolsky Ceramic Plant, prototypes of ceramic bricks with a composite additive of coal-containing components (peat) and chemical water treatment deposits were made. Studies of the physical and mechanical properties of the prototypes showed that the resulting ceramic brick corresponds to STB 1160-99 «Ceramic bricks and stones. Specifications ». Целью работы являлась оценка эффективности использования композиционной добавки на основе осадков химводоподготовки ТЭЦ и углесодержащих компонентов (торфа) при изготовлении керамического кирпича. Рассмотрена целесообразность использования торфосодержащих компонентов в сочетании с непрокалёнными осадками химводоподготовки теплоэлектроцентралей в качестве добавки в керамическую массу при производстве различных изделий. Представлено решение технической задачи введением в стандартную керамическую массу для производства строительного кирпича, дополнительно торфа фракции 0,5–5 мм в количестве 2–3,5 мас.% и непрокаленных осадков химводоподготовки теплоэлектроцентралей в количестве до 10 мас.%. На ОАО «Обольский керамический завод» изготовлены опытные образцы керамического кирпича с композиционной добавкой углесодержащих компонентов (торфа) и осадков химической водоподготовки. Исследования физико-механических свойств опытных образцов показали, что полученный керамический кирпич соответствует СТБ 1160-99 «Кирпич и камни керамические. Технические условия».